Penerapan Algoritma C4.5 Untuk Menentukan Kepuasan Pengguna Aplikasi E-Open Study Kasus : Kelurahan Jati Makmur - Komalasari, Yuli; Puspitasari, Nabila Rahmah; Chalimatusadiah, Chalimatusadiah (LPPM Universitas Bina Sarana Informatika, 2024)
To support government administration activities in an area, an application called E-Open is needed. The application was created to support the Bekasi City government, one of which is Jatimakmur Village, which is a government agency in Pondok Gede, Bekasi City. The application has been implemented, evaluation of the administration process using the E Open application is required. The aim is to measure, help, test and analyze the level of satisfaction using the E-Open application for Jatimakmur Village residents. Using data mining in data processing to determine the accuracy of each process, accurately converting information so that information is quickly understood and includes collecting, using historical data, patterns or relationships in large data sets. The research population was taken as 150 samples. Quantitative research using the C4.5 algorithm method is used, because it can make predictions by providing an ideal level of accuracy for prediction. Test this research with RapidMiner version 10.1. The results of the processing have a significant effect in determining the classification of the level of citizen satisfaction with the E-Open application. With an accuracy level of 91.33%, while in manual calculations the accuracy was 90.67% for the Satisfied percentage, or also known as the Very Good category. Keywords : Accuracy, C4.5 Algorithm,E-Open